2012
DOI: 10.1007/s10337-012-2200-1
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Scale Recovery of Phycocyanin from Spirulina platensis Using Expanded Bed Adsorption Chromatography

Abstract: The use of expanded bed adsorption chromatography (EBAC) for pilot scale recovery of C-phycocyanin (C-PC) from the cyanobacteria Spirulina platensis is described. The description includes the whole procedure, from small-scale method optimization to pilot scale. Initially, the phycobiliproteins are extracted by osmotic shock and separated by applying the centrifuged cell suspension to an EBAC column, using Streamline-DEAE as adsorbent. Next, the PCs rich solution is eluted to finally be purified by packed bed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…It shows therapeutic properties such as anti-inflammatory and hepatoprotective effects, as well as anti-oxidant capacity (Romay et al 1998). Several methods have been used for the purification of Cphycocyanin, especially that from Spirulina, such as ammonium sulfate precipitation, membrane processes and different chromatographic methods (Minkova et al 2003;Silveira et al 2007;Chaiklahan et al 2011;Bermejo and Ramos 2012). C-phycocyanin with a purity of 0.7 is considered as food grade, 3.9 as reactive grade and above 3.9 as analytical grade (Herrera et al 1989;Rito-Palomares et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…It shows therapeutic properties such as anti-inflammatory and hepatoprotective effects, as well as anti-oxidant capacity (Romay et al 1998). Several methods have been used for the purification of Cphycocyanin, especially that from Spirulina, such as ammonium sulfate precipitation, membrane processes and different chromatographic methods (Minkova et al 2003;Silveira et al 2007;Chaiklahan et al 2011;Bermejo and Ramos 2012). C-phycocyanin with a purity of 0.7 is considered as food grade, 3.9 as reactive grade and above 3.9 as analytical grade (Herrera et al 1989;Rito-Palomares et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Crude extract of C‐phycocyanin was purified by expanded bed ion exchange chromatography with two different supports: Streamline DEAE and Streamline Q XL. The Streamline DEAE has been used in C‐phycocyanin purification with an expanded bed; however, most reports mention clarified extract . Supports, such as Q XL, have only recently been used since few authors have reported their uses …”
Section: Resultsmentioning
confidence: 99%
“…The Streamline DEAE has been used in C-phycocyanin purification with an expanded bed; however, most reports mention clarified extract. [26][27][28] Supports, such as Q XL, have only recently been used since few authors have reported their uses. [20,21] Employing unclarified extracts in EBC processes without dilution usually causes flow disturbance and unequal sample distribution due to its high viscosity.…”
Section: Resultsmentioning
confidence: 99%
“…Silveira et al (2008) , respectively. The values for Q m of the same support and target productStreamline DEAE and C-phycocyanin, respectivelyfor different cyanobacteria are variable, and values for Q m of 0.8 mg.mL −1 (Bermejo et al, 2006), 1.6 mg.mL -1 (Bermejo and Ramos, 2012), 1.74 mg.mL −1 (Ramos et al, 2010) and 5.2 mg.mL −1 (Ramos et al, 2011) can be found in the literature. Thus the Streamline DEAE resin showed maximum adsorption 7 times greater than the maximum value mentioned above, reflecting the importance of studying the adsorption conditions better, for instance the influence of pH and temperature.…”
Section: Adsorption Isothermmentioning
confidence: 99%
“…Silveira et al (2008) studied the effects of pH and temperature on the partition coefficient, and determined the adsorption isotherm under the best conditions evaluated for the adsorption of C-phycocyanin onto the ion exchange resin Q-Sepharose FF, a widely used and highly successful resin applied in fixed beds. Adsorption in an expanded bed resin of Streamline DEAE was studied by Bermejo et al (2006), Ramos et al (2010), Ramos et al (2011) and Bermejo and Ramos (2012), obtaining the adsorption isotherms for crude C-phycocyanin and/or a purified extract to obtain the parameter Q m . In these studies the kinetic behavior was not evaluated and the pH and temperature were not optimized for better adsorption.…”
Section: Introductionmentioning
confidence: 99%